Consumption of online services : consumption of information good & team performance in online gaming - Xiao, Yuhong (2017)
Developments in Information Technology has resulted in novel ways to consume products and services over the internet. In this thesis, we looked specifically at the purchase and consumption of information good bundles, and the profession online-gaming scene. Technology has enabled the purchase and consumption of information goods (e.g. music, journal articles, movies, books) to be done entirely through various digital platforms (e.g. computers, tablets and mobile devices). This has allowed sellers to price differentiate customers based on usage of the information good. Contrary to traditional context of sale where consumption quantity has little economic implication, the consumption quantity of information good on digital platforms has direct cost implication to the seller. In addition, it is presumptuous to suppose that purchase quantity translates fully to consumption quantity. It is therefore important to explore the potential biases that influences valuation and consumption differently. We are concerned with how varying quantity of good can affect valuation and consumption quantity. We discover that quantity of good is a difficult to evaluate attribute and can result in the increase of valuation when varying quantities are compared. We also discover that a quantified quantity (as opposed to unlimited) results in salience of unrealized consumption, and attempts to avoid losses results in higher consumption quantity. Concurrently, quantities that are unreasonable for the consumption context reduces the motivation to avoid loss by suggesting that losses is acceptable in the context. We ran 4 controlled experiments with about 500 participants to study the phenomenon. The competitive E-sports scene has followed the development trajectory of traditional competitive sports (e.g. basketball, football, hockey). Many professional players now compete in the scene with salaries paid by their teams as they compete in tournaments with million-dollar prize pool. Motivated by clear monetary benefits, the E-Sports scene provides a natural setting of intact teams for the study of performance of teams. In addition, software patches are periodically applied to most competitive E-sports games. The patches introduce changes to in-game variables and affects how professional players approach the game. As the changes are often introduced centrally game companies, it furthers provides the opportunity to study team performance while controlling for environmental uncertainty. The scene is characterized by a relatively unchanging team performance measure (to win the game). This allows us to study how task experience at the team-level impacts team performance. Literature review reveals that team average task experience and diversity in team task experience have not been studied in diversity research as a moderating variable and a main variable respectively. Focusing on task experience, which reveals quality of cognitive resources, we also study diversity in nationality, which reveals the quantity of unique cognitive resources in a team, and its impact on team performance. We discover that both diversity in task experience and team nationality improves team performance albeit for different reasons. Diversity in team task experience helps in the establishment of hierarchy within teams as it indicates differences in perceived expertise with regards to the team task. While average team task experience improves team performance, it was found to weaken the relationships between the two earlier mentioned diversity variables and team performance. Evidence supporting the findings were found in a dataset of 15,953 professional games played between August 2011 to February 2015.